Synthesis and Synthetic Applications of Stannylated Amino Acids and Peptides - Kazmaier, Uli (Synlett, 2025)
Amino acids and peptides with stannylated vinyl or aryl side chains are interesting synthetic building blocks that can be easily modified by cross-couplings and metal–halogen exchange reactions, whether for the synthesis of complex natural products and active ingredients or for radiolabeling. The article provides an overview of the new methods and applications.
Keywords: Amino acids; Cross-couplings; Hydrostannylations; Peptides; Stannanes